Neural networks for the analysis of mine-induced building vibrations - Kuźniar, Krystyna (Computer Assisted Methods in Engineering and Science, 2011)
A study of the capabilities of artificial neural networks in respect of selected problems of the analysis of mine-induced building vibrations is presented. Neural network technique was used for the prediction of building fundamental natural period, mapping of mining tremors parameters into response spectra from ground vibrations, soil-structure interaction analysis, simulation of building response to seismic- type excitation. On the basis of the experimental data obtained from the measurements of kinematic excitations and dynamic responses of actual structures, training and testing patterns of neural networks were formulated. The obtained results lead to a conclusion that the neural technique gives possibility of efficient, accurate enough for engineering, analysis of structural dynamics problems related to mine-induced excitations.